(untitled) (Journal of Veterinary Medicine and Animal Production, 2023)
The purposes of this experiment were to study the effect of three different environmental conditions (hot, cool, and natural) in the chicken behavior as indicated by duration of tonic immobility, and the role of dietary nucleotide supplementation on elevate the stress. A total of 135 unsexed commercial chickens at fourteen-day of age were divided into three different environmental conditions; hot environment (H) with ambient temperature 32±1°C, comfortable environment (C) with ambient temperature 23 ±1°C, and natural environment (N). The chicken in every environment condition received a basal diet supplemented with three levels of nucleotide (0 g/kg) as a control group (T0), T1; 1 g/kg, and T2; 0.5 g/kg. Birds were fed ad libitum until slaughter at 35 days. The duration of tonic immobility was evaluated two times on age 25 day and 34 day. The result of this study revealed that chicken reared under natural environment temperature increase the duration of tonic immobility compare with chicken’s rear under hot and comfortable environmentcondition. Based on the results of this study it was concluded that the supplementation of dietary nucleotide has no effect on reducing the stress behavior.